(3GdETJbGbs - (3GHf OQjO , CHh HcQ eMeO Hf GdMSf Hf OQjO GdCROj, GHf OQjO,J (B321 (3g` s ((3CMeO Hf YHO GdbGOQ Hf CMeO Hf ecJhe GdbjSi s)
(3ChdgG (B:s
(3Chd GdehLhO efg , bjd GdYJHi eG HGd GdYQH SeYJ GHfGAgG HGdCSeGA GdeSJTfYI hSeJ YHjOgG HGdCSeGA GdeSJMSfI ? s
(3BNQgG (B:s
(3Obje (B: (3GSe , hgh JUZjQ Obe , ef bhdge (B: (3ObeJ aGg ObekG (B: (3EPG cSQJg Je cJGH GdGTJbGb s
(3HgG fXGe GdJYbjHIs
(3Jhai GdfGSN SfI (B749 (3hgh UGMH cJGH GdOQGddbjW ef JaSjQ GdHMQ GdeMjW GdChQGb GdChdi eeRbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B189 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B32s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GddZIs